Guest editorial: games for learning and dialogue on humanitarian work - Casper Harteveld; Pablo Suarez (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – – The purpose of this guest editorial is to provide the introduction and context of the Special Issue on Games for Learning and Dialogue on Humanitarian Work. The Special Issue aims to promote the development, deployment, and analysis of games for the humanitarian sector: it investigates how games can meaningfully engage people and organizations in experiencing, understanding and improving complex systems. Design/methodology/approach – – The editorial describes the need and motivation for building a body of knowledge on the use of games in the humanitarian sector. It further gives an overview of the three papers included in this Special Issue and how they contribute to building such a body of knowledge. Findings – – Games enable participants to experience the complexity of humanitarian systems, linking decisions with consequences. Even though game-like approaches have been used for decades in disaster management, there is little written about it. The papers included in this Special Issue provide insights and frameworks to learn from, ranging from online tools that reveal inefficiencies in supply chains, to simulated emergency response exercises, to applied improvisation. In addition, the current papers highlight the need for more empirical study of the impact of games. Research implications/limitations – – The Special Issue describes three unique cases, which by no means cover the entire practice of games in the humanitarian sector. However, they do provide insight into the diversity of game-like approaches and signal the current state of practice and research of games for learning and dialogue on humanitarian work. Practical implications – – This editorial gives an overview of how games could be used in practice and why they are relevant for humanitarian work. It further highlights how the contributions in the Special Issue may help in improving humanitarian work. Originality/value – – Although review papers and Special Issues have appeared on particular topics such as climate change, to our knowledge no significant academic attention has been given to humanitarian work with regards to games.